Phenology and productivity in a montane bird assemblage: Trends and responses to elevation and climate variation. (11th January 2019) - Saracco, James F.; Siegel, Rodney B.; Helton, Lauren; Stock, Sarah L.; DeSante, David F.
Abstract: Climate variation has been linked to historical and predicted future distributions and dynamics of wildlife populations. However, demographic mechanisms underlying these changes remain poorly understood. Here, we assessed variation and trends in climate (annual snowfall and spring temperature anomalies) and avian demographic variables from mist‐netting data (breeding phenology and productivity) at six sites along an elevation gradient spanning the montane zone of Yosemite National Park between 1993 and 2017. We implemented multi‐species hierarchical models to relate demographic responses to elevation and climate covariates. Annual variation in climate and avian demographic variables was high. Snowfall declined (10 mm/year at the highest site, 2 mm at the lowest site), while spring temperature increased (0.045°C/year) over the study period. Breeding phenology (mean first capture date of juvenile birds) advanced by 0.2 day/year (5 days); and productivity (probability of capturing a juvenile bird) increased by 0.8%/year. Breeding phenology was 12 days earlier at the lowest compared to highest site, 18 days earlier in years with lowest compared to highest snowfall anomalies, and 6 d earlier in relatively warm springs (after controlling for snowfall effects). Productivity was positively related to elevation. However, elevation–productivity responses varied among species; species with higher productivity at higher compared to lower elevations tended to be species with documented range retractions during the past century. Productivity tended to be negatively related to snowfall and was positively related to spring temperature. Overall, our results suggest that birds have tracked the variable climatic conditions in this system and have benefited from a trend toward warmer, drier springs. However, we caution that continued warming and multi‐year drought or extreme weather years may alter these relationships in the future. Multi‐species demographic modeling, such as implemented here, can provide an important tool for guiding conservation of species assemblages under global change. Abstract : Based on hierarchical multi‐species models applied to avian mist‐netting data from six sites along a montane elevation gradient in a large protected area, we show advancement of avian breeding phenology (mean first capture date of juvenile birds) and increase in productivity (probability of capturing a juvenile bird) over 25 years with variable but declining snowfall and increasing spring temperatures. Breeding phenology depended on elevation and tracked climatic conditions. Productivity was higher in relatively warm springs, while productivity–elevation responses were variable among species; species with higher productivity at higher elevations tended to be species with recent range retractions.